Kedudukan Perancang Peraturan Perundang-Undangan dalam Pembentukan Peraturan Daerah - I Dewa Gede Anggarisna; I Gusti Bagus Suryawan; Luh Putu Suryani (Warmadewa Press, 2021)
This study aims to determine the position and duties of the designer in the formation of regional regulations and the implementation of the designer's participation in the formation of regional regulations in Bali Province. The method in this legal research uses empirical legal research. The results show that the position and duties of the drafters of legislation in the formation of regional regulations play an important role, namely preparing to process and formulate all legal instruments and matters related to the design of legislation, while in the formation of regional regulations in Bali Province, the implementation of participation, namely the statutory designer is still there are 3 regencies / cities that have not involved the designer in the formation of local regulations. The comparison of the number of perda revoked from 2014-2019 between Provinces / Districts that involve designers and districts / cities that have not involved designers does not show a significant comparison of numbers. However, in 2018 the implementation of Designer Participation. In the Formation of Regional Regulations in the Province of Bali, it was started from the beginning to the end. So that the implementation of the participation of the new designer begins to run effectively. The legal consequence is that if the designer does not explicitly include the statutory regulations it does not explicitly state the sanctions so that there is an empty norm.